HORMONAL LEVELS AND FOLLICULAR DYNAMICS IN RELATION TO THE OESTROUS CYCLE IN BARB AND ARABIAN MARES, ALGERIA - HOUSSOU Hind; BOUZEBDA AFRI Farida; BOUZEBDA Zoubir (SCIENDO, 2021)
This current study is an effort to understand the hormonal and follicular growth in the Barb and Arabian mares during the oestrous cycle; as mares are unique creatures. A total of 53 mares with 97 oestrous cycles were studied. The mares with a mean age of 10.38 ± 4.55 were examined by ultrasonography every day during their breeding season (2017). Two blood samples from each mare (n = 24) were obtained for progesterone (P4), oestrogen (oestradiol-17 beta) and follicle-stimulating hormone (FSH) determinations. The data revealed that the duration of the oestrous cycle was between 19 to 22 days. The pre-ovulatory follicle grew (3.02 ± 1.04) millimetre per day. The rate of cycles exploited in the mare (Arabian versus Barb) for conception was significantly different (P < 0.001). The maximal diameter of the follicle was 50.00 millimetre. The serum progesterone levels (P < 0.01) in mares were significantly higher in the luteal phase than those recorded during the time of oestrous. However, the levels of oestradiol and for FSH did not significantly change during the oestrous cycle in the mares. Determining the association between the size of the follicle and the hormone profiles were the most reliable criterion in the prediction of ovulation.